A pilot test on how motivation can influence performance in the field of European project writing - Ionescu, Anca-Maria; Stănescu, Monica; Aivaz, Kamer-Ainur (Technium Social Sciences Journal, 2022)
This pilot study analyzes how participants’ motivation in a training intervention for public sports organizations influences their performance in European project writing. Our specific assumption is that performance in attracting projects with non-reimbursable funds is higher for people with a higher motivation level. The approach used in this pilot research was the individualization of success cases – organizations that either made project drafts following the European project writing training or submitted and won projects through the Erasmus+ program. The collection of quantitative data was performed using motivation tests (Achievement Motivation Inventory - AMI) that helped us to understand better the evaluated person in terms of their performance orientation and the way their motivation is articulated. There were about 40 participants involved in the training at the beginning, with only about 30 active participants throughout the training period. Eight of the 14 participants who completed the AMI test made project drafts. From the analyzed data, it emerges that people with a developed or strong average motivational index made project drafts or submitted applications within the Erasmus+ program. In contrast, the persons with a lower motivational index did not make a project draft nor submit applications to the Erasmus program. However, due to the small number of AMI tests completed, we cannot generalize this to all course participants. Further research should be done on other factors determining performance in writing European projects.